Greater small nerve fibre damage in the skin and cornea of type 1 diabetic patients with painful compared to painless diabetic neuropathy. (23rd February 2021) - Ferdousi, Maryam; Azmi, Shazli; Kalteniece, Alise; Petropoulos, Ioannis Nikolaos; Ponirakis, Georgios; Asghar, Omar; Alam, Uazman; Marshall, Andrew; Boulton, Andrew J. M.; Efron, Nathan; Soran, Handrean; Jeziorska, Maria; et al.
Abstract: Background and aim: Damage to small nociceptive fibres may contribute to painful diabetic neuropathy. We aimed to compare large and small nerve fibre measurements together with skin biopsy and corneal confocal microscopy in patients with type 1 diabetes and painful or painless diabetic neuropathy. Methods: We have assessed the McGill pain questionnaire, neuropathy disability score, vibration perception threshold, warm and cold sensation thresholds, electrophysiology, corneal confocal microscopy and skin biopsy in participants with type 1 diabetes and painful ( n = 41) or painless ( n = 50) diabetic neuropathy and control subjects ( n = 50). Results: The duration of diabetes, body mass index, glycated haemoglobin (HbA1c), blood pressure and lipid profile did not differ between subjects with painful and painless neuropathy. Neuropathy disability score and vibration perception threshold were higher and sural nerve conduction velocity was lower, but sural nerve amplitude, peroneal nerve amplitude and conduction velocity and cold and warm sensation thresholds did not differ between patients with painful compared to painless diabetic neuropathy. However, intraepidermal nerve fibre density, corneal nerve fibre density, corneal nerve branch density and corneal nerve fibre length were significantly lower in subjects with painful compared to painless diabetic neuropathy. Conclusions: There is evidence of more severe neuropathy, particularly small fibre damage in the skin and cornea, of patients with painful compared to painless diabetic neuropathy. Abstract : Damage to small nociceptive fibres may contribute to painful diabetic neuropathy. This study compared measures of large and small nerve fibres in patients with type 1 diabetes and painful or painless diabetic neuropathy. There is evidence of more severe neuropathy, particularly small fibre damage in the skin and cornea of patients with painful compared to painless diabetic neuropathy.